DEVELOPMENT OF MODULE ELEMENTARY LINEAR ALGEBRA INTEGRATED TO MEDIA PREZI FOR PRE-SERVICE MATHEMATICS TEACHER - Siahaan, Meiva Marthaulina Lestari; Fitriani, Fitriani; Samo, Damianus Dao; Nenohai, Juliana M.H. (FKIP Universitas Muhammadiyah Tangerang, 2024)
This study purposed to describe the development and produce elementary linear algebra course modules on system of linear equation (SLE) and matrices integrated with Prezi learning media that are valid, practical and effective. This development research referred to the development design steps developed by Allesi & Trollip. The development design is grouped into three development procedures, which include: planning, design, and development stage. The product trial consisted of an alpha test conducted by two material experts and two media experts, as well as a beta test which was carried out through 2 stages, beta test 1 (small group trial) to 8 subjects; representatives of two students at cohort 2019/2020, 2020/2021, 2021/2022, and 2022/2023. Beta test 2 was conducted on 70 students who took the Elementary Linear Algebra course in cohort 2023/2024. Data collection used questionnaires for material experts, questionnaires for media experts, student response questionnaires, and tests. The developed module has several advantages. First, the material is prepared based on the results of research that has been done in previous studies so that it can minimize epistemological learning obstacles. Second, it is integrated with Prezi-based learning media that supports a deeper understanding of SLE content material.